2020
DOI: 10.1038/s42003-020-0775-x
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosomatid parasite dynamically changes the transcriptome during infection and modifies honey bee physiology

Abstract: It is still not understood how honey bee parasite changes the gene expression to adapt to the host environment and how the host simultaneously responds to the parasite infection by modifying its own gene expression. To address this question, we studied a trypanosomatid, Lotmaria passim, which can be cultured in medium and inhabit the honey bee hindgut.We found that L. passim decreases mRNAs associated with protein translation, glycolysis, detoxification of radical oxygen species, and kinetoplast respiratory ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 79 publications
7
43
0
Order By: Relevance
“…These results indicate that L. passim does not induce a rapid death of the host compared with N. ceranae , although this assertion should be taken with caution, considering that the initial levels of L. passim in infected bees were lower (1.0 ± 0.6 × 10 3 cell per bee) than the levels of N. ceranae (1.0 ± 0.3 × 10 5 spores per bee) that healthy bees were inoculated with. However, our results were similar to a report by Liu et al [ 41 ], who found that the accumulation of L. passim in the hindgut slightly decreased the honey bees’ survival but never resulted in rapid death.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that L. passim does not induce a rapid death of the host compared with N. ceranae , although this assertion should be taken with caution, considering that the initial levels of L. passim in infected bees were lower (1.0 ± 0.6 × 10 3 cell per bee) than the levels of N. ceranae (1.0 ± 0.3 × 10 5 spores per bee) that healthy bees were inoculated with. However, our results were similar to a report by Liu et al [ 41 ], who found that the accumulation of L. passim in the hindgut slightly decreased the honey bees’ survival but never resulted in rapid death.…”
Section: Discussionsupporting
confidence: 93%
“…In that regard, it should be noted the importance of the initial cell concentration of the cultures: differences in the starting concentration could involve variations on the time needed to reach the same growth phase. For instance, in Gómez – Moracho et al (2020) , the initial culture concentration was 10 6 cells/mL, reaching the early stationary phase after 96 h; whereas in our case study, the initial concentration of the culture was 10 5 cells/mL, hence the cells were in that same growth phase at 168 h. There have also been variations in the culture media, the age of the bees (post-emergence) at the time of infection (e.g., 5 days-old in Gómez-Moracho et al, 2020 and Higes et al, 2016 , yet 2-3 h-old bees in Liu et al, 2020 ), and in the administration method (individually or collectively). Moreover, the temperature at which the bees are maintained after infection (varying between 27 °C and 33 °C) might cause some disparity in the results, particularly since this aspect has been considered a key factor in the morphological changes to other trypanosomatid species, such as the genus Leishmania ( Darling and Blum, 1987 ; Stinson et al, 1989 ).…”
Section: Resultsmentioning
confidence: 63%
“…However, there is no consensus as to the precise influence that these protozoans might have on bee health, at either the individual or the colony level. The majority of studies to date have focused on different protocols to detect trypanosomatid prevalence and diversity ( Arismendi et al, 2016 , Bartolomé et al, 2018 , Bartolomé et al, 2020 , Vejnovic et al, 2018 , Xu et al, 2018 ), yet few have investigated the mortality rates they produce following experimental infection by different isolates and species ( Gómez-Moracho et al, 2020 ; Higes et al, 2016 ; Liu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations